2011
DOI: 10.3109/00016357.2011.600712
|View full text |Cite
|
Sign up to set email alerts
|

Quality and contents of referral letters from peripheral health centers to the dental centre of a teaching hospital, southwestern Nigeria

Abstract: This study has shown that referral letters written from various peripheral healthcare centers to the dental centre of a teaching hospital is generally of unacceptable quality and the content could be improved upon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 7 publications
2
15
0
1
Order By: Relevance
“…6 Referral documents are important and quite common instruments for exchange of information between professionals from different health care levels. 7,8,9 In some situations, referral documents are the only means available for this exchange, 10,11,12 and may also affect the quality of care offered to the patients. 9,10,13 The quality of these documents is therefore essential for proper health care, and its contents should allow assessing the clinical need and the urgency for appointments.…”
Section: Introductionmentioning
confidence: 99%
“…6 Referral documents are important and quite common instruments for exchange of information between professionals from different health care levels. 7,8,9 In some situations, referral documents are the only means available for this exchange, 10,11,12 and may also affect the quality of care offered to the patients. 9,10,13 The quality of these documents is therefore essential for proper health care, and its contents should allow assessing the clinical need and the urgency for appointments.…”
Section: Introductionmentioning
confidence: 99%
“…9 In order to be useful, referral documents must provide organized information, rhetorical relevance, appropriate level of detail, and be concise. 12,14 However, several studies have reported that referral letters often lack important information, 7,8,9,10,12,13,15,16 which can result in problems such as improper scheduling, prioritization errors, 9,11,13 unnecessary repetition of tests 7 and, ultimately, inadequate care and delay in treating the illness. 10 Several studies aimed at defining the necessary information for the referral of patients.…”
Section: Introductionmentioning
confidence: 99%
“…12,14 However, several studies have reported that referral letters often lack important information, 7,8,9,10,12,13,15,16 which can result in problems such as improper scheduling, prioritization errors, 9,11,13 unnecessary repetition of tests 7 and, ultimately, inadequate care and delay in treating the illness. 10 Several studies aimed at defining the necessary information for the referral of patients. 8,9,10,12,16,17 Depending on the specialty, the clinical description of the lesion is considered essential.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations